A Short Synthesis of the Mould Metabolite (R)-(+)-Carolinic Acid from (S)-Lactic Acid - Linder, David; Schobert, Rainer (Synthesis, 2016)
(R)-(+)-Carolinic acid was prepared in seven steps and 59% yield from inexpensive benzyl l-lactate, the configuration of which was inverted by a Mitsunobu reaction with trifluoroacetate. The resulting benzyl d-lactate was cyclised by a domino addition–Wittig alkenation reaction with Ph3PCCO. The product tetronic acid was acylated with a second equivalent of this ylide to give a 3-acylylidenetetronic acid, which was olefinated directly with tert-butyl glyoxylate. The product alkene was hydrogenated and deprotected to afford pure crystalline (R)-(+)-carolinic acid, which proved inactive against Staphylococcus aureus and Escherichia coli mutant D21f2.
Keywords: tetronic acids; carolinic acid; Wittig reaction; natural products; stereoinversion